Concentric left ventricular remodeling and aortic stiffness: a comparison of obesity and hypertension. - Rider, O; Nethononda, R; Petersen, SE; Francis, J; Byrne, J; Leeson, P; Clarke, K; Neubauer, S (2013)
BACKGROUND: Increased thoracic ascending aortic stiffness is thought to contribute to concentric left ventricular hypertrophy and increased mortality, a pattern seen in hypertension. As such, aortic stiffness and increased left ventricular mass are candidates by which obesity increases cardiovascular risk. However, obesity is characterized predominantly by increased abdominal aortic stiffness and with eccentric left ventricular hypertrophy. METHODS: We aimed to establish whether or not, in addition to these changes, there is also an element of concentric remodeling in obesity that was predicted by ascending aortic stiffness. 301 subjects underwent cardiovascular magnetic resonance imaging to measure regional aortic distensibility and left ventricular morphology. To compare obesity with hypertension, subjects were separated into groups by hypertensive status and body mass index. RESULTS: In comparison to normotensive subjects, hypertension was linked with concentric remodeling (a 17% increase in left ventricular mass:volume ratio (LVM:VR), (p<0.001)) and reduced ascending aortic distensibility (by 64%,p<0.001). LVM:VR was negatively correlated with ascending aortic distensibility (R=-0.36,p<0.01). Obesity, in the absence of hypertension, was associated with elevated left ventricular mass when compared to normal weight normotensive subjects (by 27%, p<0.01), in an eccentric pattern with cavity dilatation (p<0.01). However, LVM:VR was also 14% larger than in normal weight normotensive subjects (p<0.01), indicative of additional concentric remodeling. LVM:VR in obesity was, however, not correlated with ascending aortic distensibility when adjusted for mean arterial pressure (R=-0.14,p<0.14). CONCLUSION: In summary, despite the predominantly eccentric pattern of left hypertrophy in obesity there is a concentric element of hypertrophy that, unlike in hypertension, is not linked to increased ascending aortic stiffness.